Conference report on the 1st US–Japan workshop on power and particle control by liquid metal plasma-facing components in a steady state magnetic fusion DEMO reactor. (12th November 2019) - Hirooka, Y.; Ono, M.; Maingi, R.; Hanada, K.; Kondo, M.; Miyazawa, J.; Shimada, M.
Abstract: As part of the US–Japan bilateral collaboration program, a new series of workshops have been inaugurated on the subject of 'Power and Particle Control by Liquid Metal Plasma-Facing Components in a Steady State Magnetic Fusion DEMO Reactor'. The first workshop of this series was held at Princeton Plasma Physics Laboratory on 11–13 March 2019. This conference report is intended to share 24 technical presentations, discussion and the planning of future workshops with the world magnetic fusion community.